Cytomegalovirus pneumonitis-induced secondary hemophagocytic lymphohistiocytosis and SIADH in an immunocompetent elderly male literature review. (2020) - Patil, Sachin M.; Beck, Phillip Paul; Patel, Tarang Pankaj; Hunter, Michael P; Johnson, Jeremy; Acevedo, Bran Andres; Roland, William
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is also known as hemophagocytic syndrome. It is a lethal hematologic condition due to a dysregulated immune response which results in inappropriately activated macrophages damaging host tissues. Based on the etiology, HLH can be primary (genetic) or secondary (acquired). The most common cause of a secondary HLH is an infection. Viral infections are the most common cause of secondary HLH. Among the viral causes of secondary HLH, Epstein–Barr virus is the most common etiologic agent. Cytomegalovirus (CMV) is a common causative pathogen in the immunocompromised host but is rare in an immunocompetent adult. In infection- associated secondary HLH, treatment includes antimicrobial therapy. HLH carries a high mortality and morbidity rate as it is an underdiagnosed clinical condition. Successful early diagnosis allows for adequate time for curative therapy. Treatment for HLH includes chemotherapy, immunomodulators, and a hematopoietic stem-cell transplant. The 2004 diagnostic criteria set by the Histiocyte Society serves as a guide to make an earlier clinical diagnosis. A review of PubMed literature revealed only five reported cases of CMV-induced HLH. We describe the sixth case of CMV pneumonitis-induced HLH and syndrome of inappropriate antidiuretic hormone secretion in a 72-year-old White male. He was treated successfully with oral valganciclovir and corticosteroids.